Effects of utilizing MSW leachate as mixing water on setting time and strength of blended cement mortar and concrete - Chua, Mark Hansley Y. (2006)
Construction scenarios requiring cast-in-place or mat foundations near disposal facilities risk contamination of cement before it sets. Knowledge of the effects on some basic physical properties would be useful. The study shows that using mortar mixes with varying concentrations of leachate (derived from one of the post of the Payatas Municipal Solid Waste Facility) in the mixing water generally increases time of setting and decreases the compressive strength of Blended Cement Type IP. This is true for mortars with water to cement (W/C) ration of 0.3, 0.485, and 0.7. Based on ASTM C160/C 1602M-04, the allowable leachate concentration in mixing water for W/C 0.3 is 80% for 0.485 is 20%, and 0.7 is between 10-30%. Samples were examined using Toxicity Characteristic Leaching Procedure (TCLP) to find out how much of the heavy metals (i.e. Lead and Chromium) are immobilized. Concentrations of leachate in mixing water higher than 80% for Chromium and 50% for Lead exceed their respective drinking water standards. Lastly, concreate mixes were made on the optimum mix designs for each. At 28 days, 100% leachate mixing liquid has 18% strength reduction for W/C 0.485 and 31% strength reduction for W/C 0.7. Lead was successfully immobilized and Chromium was still found a bit more than the drinking water standards.